EVALUATION OF MONOLAYER MOISTURE CAPACITY AND THE ENERGY CONSTANT OF SOME POWDERED SPICES BY USING BET AND GAB MODELS - M Arpah; E Diyah (Jurnal Teknologi dan Industri Pangan, 2004)
BET equation (IUPAC standard) and GAB equation (European Project Group on physical properties of food recommendation standard) for monolayer capacity value evaluations were used for testing the moisture adsorption experimental data of powdered white and black papper, cloves, nutmeg and cinnamon. The BET equation fits only up to aw = 0.44, while the GAB isotherm fits and covers a much wider range (0.06